Substantial Increases in Eastern Amazon and Cerrado Biomass Burning‐Sourced Tropospheric Ozone. Issue 3 (3rd February 2020) - Pope, Richard J.; Arnold, Stephen R.; Chipperfield, Martyn P.; Reddington, Carly L. S.; Butt, Edward W.; Keslake, Tim D.; Feng, Wuhu; Latter, Barry G.; Kerridge, Brian J.; Siddans, Richard; Rizzo, Luciana; Artaxo, Paulo; et al.
Abstract: The decline in Amazonian deforestation rates and biomass burning activity (2001–2012) has been shown to reduce air pollutant emissions (e.g., aerosols) and improve regional air quality. However, in the Cerrado region (savannah grasslands in northeastern Brazil), satellite observations reveal increases in fire activity and tropospheric column nitrogen dioxide (an ozone precursor) during the burning season (August‐October, 2005–2016), which have partially offset these air quality benefits. Simulations from a 3‐D global chemistry transport model (CTM) capture this increase in NO2 with a surface increase of 1 ppbv per decade. As there are limited long‐term observational tropospheric ozone records, we utilize the well‐evaluated CTM to investigate changes in ozone. Here, the CTM suggests that Cerrado region surface ozone is increasing by 10 ppbv per decade. If left unmitigated, these positive fire‐sourced ozone trends will substantially increase the regional health risks and impacts from expected future enhancements in South American biomass burning activity under climate change. Key Point: Savannah‐type fires in the Cerrado, northeastern Brazil, have increased emissions of ozone precursor gases degrading air quality